Covalent immobilization of aminoacylase to alginate for L-phenylalanine production - Lee, Pat M.; Lee, Kong H.; Siaw, Yew S. (Wiley, 1993)
Aminoacylase I (EC. 3.5.1.14) was immobilized by covalent crosslinking to alginate molecules with 1‐ethyl‐3‐(3‐dimethyl‐aminopropyl)‐carbodiimide HCl followed by calcium alginate bead formation for the production of L‐phenylalanine from the racemic mixtures of N‐acetyl‐DL‐phenylalanine. Different concentrations of the coupling reagent were tested and the coupling process was optimized. The immobilized and the partially purified aminoacylase were characterized in terms of the activity, operational stability, thermal stability, pH and temperature optima and kinetic constants, Km and Vmax. The activity of the enzyme covalently immobilized in calcium alginate beads was enhanced by about 75% compared to that of free enzyme. The beads showed stable activity under operational conditions, they lost about 40% of their activity after four reaction cycles. The immobilized aminoacylase was more stable over a broader pH range. Thus this simple method provides irreversible immobilization of aminoacylase to give a biocatalyst with good operational stability and enhanced activity.